THE SOCIOCULTURAL IMPACT OF ARABIC PERSONAL NAMES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Arabic anthroponyms, as a social factor, play a significant role in shaping and reflecting the social structure and relationships within Arab society. They not only help identify individuals but also express their social identity, heritage, and status within the community. Through the use of specific naming conventions, such as patronymics, individuals are linked to their family, tribe, and broader social groups, which reinforces societal cohesion and continuity. These names often reflect the individual's lineage, social position, and adherence to cultural and religious norms, making them a vital element in maintaining social order and connections.